PKM melalui Pendampingan bagi Guru Mata Pelajaran Fiqih BAB Thoharoh - Aufia Aisa; Amrini Shofiyani; M. Jauharul Eka M.; M. Farkhanudin (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2021)
The purpose of this community service activity is to provide assistance regarding 1) Suitable learning materials in the subject of fiqh chapter Thoharoh, 2) classroom management, 3) improvement of teacher skills in using learning methods. To achieve these objectives, several activities were carried out including 1) training in the preparation of learning tools, 2) improving the learning methods of fiqh in the thoharoh chapter. This community service activity was carried out at MI Darul Ma'arif in the village of Brodot. The result of this activity is the realization of learning in accordance with the learning guidelines with the preparation of lesson plans, the availability of educational media for learning fiqh.